Physiological and Psychological Effects of 8 Weeks of Aikido Exercises in Young Individuals - Mehmet SARUHAN; Özhan BAVLI (ümit doğan üstün, 2023)
The aim of this study is to investigate the effects of 8 weeks of Aikido exercises on static balance, resting heart rate, aggression, state anxiety, and self-confidence levels in young individuals. The study included 30 volunteers with an average age of 20.47 ± 1.52 years, average height of 167 ± 9.8 cm, and average weight of 60.1±8.58 kg, who had not previously participated in Aikido exercises. Participants were voluntarily enrolled in the study and received basic Aikido exercises twice a week for 90 minutes, administered by a licensed instructor, over the course of 8 weeks. Resting heart rate measurements, static balance performance, aggression, state anxiety, and self-confidence scores of the participants were assessed before and after the study. The Flamingo balance test, pulse rate test, Buss-Perry Aggression Scale (1992), Self-confidence scale (Akın 2007), and State Anxiety Scale (Spielberger et al., 1970) were used as data collection tools. The SPSS program was used for data analysis, and findings were considered significant at p<0.05. As a result of the analyses, it was concluded that there was a significant difference in all categories except resting heart rate scores between pre- and post-study measurements (p<0.05). When comparing genders, no statistically significant differences were observed in terms of all observed variables (p>0.05). Based on these findings, it can be stated that 8 weeks of Aikido exercises can be a preferred exercise method to improve the static balance performance and have a positive impact on aggression, self-confidence, and state anxiety scores in young individuals.